Biometric analysis of fruits and pre-germination treatments to break dormancy in seeds of Libidibia ferrea (Mart. ex Tul.) L. P. Queiroz (Research, Society and Development, 2021)
In the semiarid region, most forest species have seeds with slow and uneven germination over time because they have dormancy. Given the above, the objective was to evaluate the biometric characteristics of fruits and seeds and the influence of pre-germinative treatments on the emergence of Libidibia ferrea seedlings. The length, width and thickness of fruits and seeds were measured. A completely randomized design was adopted, with eight pre-germinative treatments: control (no treatment); hydrochloric acid for 5, 10, 15 and 20 minutes; caustic soda for 5 and 10 minutes; mechanical scarification with sandpaper n° 150 in the region opposite the hilum and subsequent immersion in water for 24 hours. The following characteristics were evaluated: percentage, velocity index and average time of emergence, length of the root system and of the aerial part of the seedlings. The average fruit size was 7.93 mm long, 23.19 mm wide and 11.87 mm thick and 4.67 viable seeds per fruit. The use of mechanical scarification with sandpaper No. 150 in the region opposite the hilum with subsequent soaking in water for 24 h is the most indicated method for overcoming dormancy in L. ferrea.